Fluidized bed dryers - Mohd Faiz, Mohideen Batchaal; Shahrin Hisham, Amirnordin; Ahmmad Shukrie, Md Yudin
This chapter discusses one of the dryers that is widely used in the food industry—the fluidized bed dryer (FBD). Unlike other drying technologies, this involves the suspension of moisture-laden products in the drying medium (usually air). The excellent solid-fluid contact provides several advantages, such as a high heat transfer rate and thus a high drying rate, homogeneity in moisture reduction, flexibility in operation, ability to accommodate wide particle sizes, and many more. In this chapter, selected types of fluidized beds are briefly addressed followed by the advantages of FBDs in food processing. This was followed by heat and mass transfer modeling, basics in designing a FBD with a worked example, and highlights on the recent advances in FBD technology. The chapter was then summarized, concluding that FBDs are one of the preferred technologies in food processing.